Policy Analysis of The Independent Curriculum In Indonesia - Raodatul Jannah (Syntax Corporation, 2023)
The changes taking place in this world are very fast. The change affects everything in it. Including in the world of education. The condition of the world that is slowly moving back after the COVID-19 pandemic requires us to quickly respond to existing changes. For this recovery is carried out on all parties. Education in Indonesia must also move quickly to implement recovery. One of them is with curriculum changes. The independent curriculum is a curriculum used to immediately restore education in Indonesia. A curriculum that can be expected to accommodate all student needs. This independent curriculum is one of the series of the Merdeka Belajar Program launched by the government through the Ministry of Education and Culture and Technology. It takes hard work and joint effort to make Indonesia better.